"No Monuments, No Heroes": How Accidental Planners Established Bolivia's Flagship Land Reform Project through Spatial, Facilitated, and Adaptive Strategies. (December 2016) - Hoey, Lesli
The promises of land reform have always been as seductive as they are elusive. Bolivia's experience is no different, but one forgotten case may still offer lessons today: a land distribution project initiated in San Julian in 1972. Through archival research and interviews, I argue that several understudied elements of the San Julian project—its spatial design, settler orientation program and implementation process—offer lessons about the role planners can play in structuring more successful land reform. Revisiting the lessons of past exemplars like San Julian is critical given renewed land reform efforts that appear to be replicating past failures.